Educação musical e práticas corporais como recurso metodológico da educação infantil: diálogos com professores de música e educandos sobre interdisciplinaridade - Nedel, Mariana Zamberlan (2010)
This research, developed in a master degree, had as mail proposed to examine narratives of teachersof music and students of the second to fifth year of fundamental school about use of corporal practices and musical education as elements involved of the teaching-learning process of children's education and analyze the body and its use throughout the narratives of employees during the interviews; describe the type of interest, manifest in a interview, that music teachers and students have in music education combined with corporal practices; typify the difference between the teaching practices of two teachers interviewed; understanding how the body practices allied to music described by the teachers interviewed are associated with a total and integralizing education and the main contributions of teaching of this content to children in several areas of their lives. The data collection was realized in two private school at the city of Ribeirão Preto-SP, Brazil, which are: Instituto de Educação Infantil e Ensino Fundamental Liceu Albert Sabin e Instituto Santa Úrsula de Ribeirão Preto. For this research the use of the methodology Oral History became the most appropriate. Within the Oral History, was used as a resource the Thematic Oral History and Hybrid. The use of Oral History Hybrid is justified by the fact that can use the observations of the classes of teachers, film of these classes, field notes, whatever material provided by teachers, beyond the interviews semi-structured (resource of Thematic Oral History). This thesis is divided into six moments. The first theme were examined the historical moment of postmodernity. In the second are describe a brief history of interdisciplinarity, and the main features of an interdisciplinary teaching. The third moment was intended for the body and practices related to it, emphasize that the release of the body was in the times narcissism can be provided through the culture of caring for oneself and automatically another. In the fourth describes the methodologies and resources that were thought to be appropriate for the collection and analysis of data. The fifth presents the main themes and ideas raised during the data collection with two music teachers, eight learners, and classes and events observed. And in the sixth moment are describe more relevant considerations about the perceived importance of teaching based on physical practices and musical education as tools for the educational process for children. At the end of this dissertation analyzes the corporal practices coupled with the music, used for the teachers interviewed, regarding their possible features related to a total education as a whole.